145Educational inequalities in primary prevention statin use in UK Biobank. (2nd September 2021) - Carter, Alice; Gill, Dipender; Morris, Richard; Smith, George Davey; Taylor, Amy; Davies, Neil; Howe, Laura
Abstract: Background: Socioeconomic inequalities in cardiovascular disease are well documented, but the association of socioeconomic position with treatment for cardiovascular disease prevention is unclear. Methods: Using data from a large prospective cohort study, UK Biobank, we calculated QRISK3 cardiovascular risk scores for 472 097 eligible participants with complete data on self-reported educational attainment and statin use (55% female; mean age, 56). We used logistic regression to explore the association between i) QRISK3 score and ii) educational attainment on self-report statin use. We then stratified the association between QRISK3 score, and statin use by educational attainment to test for interactions. Results: For an equivalent QRISK3 score, more educated individuals were more likely to report taking statins. In women with 7 years of schooling, a one unit increase in QRISK3 score was associated with a 7% higher odds of statin use (odds ratio (OR) 1.07, 95% CI 1.07, 1.07). In women with 20 years of schooling, a one unit increase in QRISK3 score was associated with an 14% higher odds of statin use (OR 1.14, 95% CI 1.14, 1.15). Comparable ORs in men were 1.04 (95% CI 1.04, 1.05) for 7 years of schooling and 1.08 (95% CI 1.08, 1.08) for 20 years of schooling. Conclusions: Individuals with less education are less likely to access statins conditional on cardiovascular risk factors. Key messages: Inequalities in access to cardiovascular preventive medication are likely contributing to cardiovascular inequalities.